Empowering Local Governance Examining the Transfer of Land and Building Rights Acquisition Tax in Alignment with Regional Autonomy Principles - Rahma, Laela Novitri Ervia; Annisa Restu Fauziah; Muhammad Adymas Hikal Fikri (LPPM Universitas Jambi, 2024)
Taxes serve as the primary revenue source for governments, with the Transfer of Land and Building Rights Acquisition Tax (BPHTB) being a significant contributor. BPHTB is levied on transactions related to the transfer of land and building rights. While the central government initially managed this tax, the implementation of regional autonomy has shifted the responsibility for Transfer of Land and Building Rights Acquisition Tax management to local governments. This research aims to investigate the fundamental concept of local taxes in the context of regional autonomy and the role of local governments in collecting Transfer of Land and Building Rights Acquisition Tax, all within the framework of regional autonomy principles. The research methodology relies heavily on a literature review (library research) using secondary data sources, particularly legal regulations. The analysis follows interpretative principles and employs the hermeneutic method. The research findings indicate that, under the framework of regional autonomy, regions have specific rights, including the authority to impose local taxes and levies. As per the Regional Tax and Regional Levy Law, two tax types, Land and Building Tax (PBB), and Transfer of Land and Building Rights Acquisition Tax (BPHTB), previously managed by the central government, have now been transferred to local governments.